Kidney nonprocurement in deceased donors with acute kidney injury. Issue 11 (21st August 2022) - Yu, Kathleen; Husain, Syed A.; King, Kristen; Stevens, Jacob S.; Parikh, Chirag R.; Mohan, Sumit
Abstract: Background: Acute kidney injury (AKI) is common in deceased organ donors and is associated with high rates of kidney discard by transplant centers. High discard rates may consequently drive nonprocurement of these kidneys by organ procurement organizations. We aimed to study the relationship between donor AKI and kidney nonprocurement. Methods: Using U.S. registry data, we identified donors with at least one organ recovered from 2008 to 2018. We compared characteristics of donors with no kidneys procured across AKI stages, and used multivariable logistic regression to evaluate the relationship between AKI severity and kidney nonprocurement. Results: Overall 14 543 kidneys from 7620 donors were not procured, among which 93% were from donors with AKI. For 6945 donors with no kidneys procured but an extrarenal organ recovered, most had stage 3 (51%), followed by stage 1 (27%) and stage 2 AKI (15%). Nonprocured stage 3 donors were the youngest and had the lowest Kidney Donor Risk Index of all nonprocured donors. Adjusted odds of kidney nonprocurement were 1.14 (95%CI 1.02–1.27) for stage 1, 1.25 (95%CI 1.12–1.41) for stage 2, and 10.37 (95%CI 9.30–11.56) for stage 3 donors, compared to non‐AKI donors. Among donors with minimum creatinine <1.5 mg/dl, stage 2 and 3 AKI were still associated with significantly higher odds of nonprocurement. Conclusions: AKI severity is a strong risk factor for kidney nonprocurement. Efforts to address the organ shortage should focus on encouraging procurement and utilization of kidneys from deceased donors with severe AKI, given the large and rising prevalence of donor AKI and excellent transplant outcomes with these kidneys.